[World War II experiences] - James McGrath:::::::::
[00:00:00] Introduction of James McGrath to audience [00:02:17] James McGrath begins to give his lecture [00:02:30] McGrath talks about the difference between 'I' and 'me' [00:06:15] McGrath begins to read a letter from 1948 about being a POW in Camp O'Donald and participating in the Bataan Death March [00:07:58] McGrath talks about rations given to him by Japanese [00:09:10] McGrath talks about contracting dysentery during the march and being quarantined [00:11:11] McGrath talks about other diseases, like scurvy and malaria, that he contracted in camp [00:12:45] McGrath talks about how he was transported on the Japanese "Hell Ship", Oryoku Maru [00:14:41] McGrath talks about how he will talk about being moved to Korea and then to Manchuria and eventually liberated by the Russians [00:15:52] McGrath talks about how he and his shipmates were able to keep a diary on their toilet paper [00:18:00] McGrath talks about his time spent in Japanese occupied Manila and being transported on a crowded ship, the Oryoku Maru [00:20:05] Ship was picked up by American planes and fired at until dark [00:21:00] McGrath talks about how the men started to become crazy during the night time after the ship was attacked [00:21:55] McGrath talks about how ship was attacked again and the ship was abandoned [00:22:50] McGrath recounts how he helped to free men trying to abandon ship [00:23:52] McGrath jumped into water to swim ashore [00:25:00] McGrath waited ashore for days while American planes attacked Japanese forces [00:27:28] McGrath acknowledges his birthday passing during time as POW [00:30:35] McGrath arrives at San Fernando, La Union on Christmas Day [00:32:38] McGrath placed on another ship for transport [00:35:02] McGrath arrived at Takao [00:38:00] Ship that he was kept on was bombed while it was being refueled [00:38:42] McGrath hit by shrapnel but continued to help fellow soldiers [00:41:53] McGrath talks about traveling North to Japan, deaths increasing due to cold [00:43:13] Snowstorm lasted for a week until they reached Mogie, Japan [00:44:25] McGrath says his dysentery is starting to become better [00:45:40] McGrath left Mogie by street car, joined with prisoners from other camps, given box for Emperor's birthday [00:47:16] McGrath arrives in Pusan, Korea [00:49:30] McGrath talks about how amazed he was at the development of Manchuria and Korea [00:50:28] McGrath arrived in Mukden, Manchuria. It was -40 degrees [00:51:25] McGrath taken care of by British and American men in the camp who cleaned him, fed him, and gave him books [00:52:16] McGrath begins to talk about sense of values again, passes out a test to all those attending the lecture [00:54:42] McGrath leaves book written by Sydney Stuart about the same journey as a POW [00:57:20] McGrath talks about a letter written by young woman who was saddened by a man who lied about being homosexual to avoid the draft [01:01:00] McGrath talks about the people who died for freedom and the need to change some sense of values in our society [01:01:15] McGrath talks about the value for education and family [01:02:29] Applause and beginning of questions from the audience [01:02:45] McGrath talks about how he managed to stay alive [01:05:20] McGrath talks about women in the camps [01:08:34] McGrath talks about religion, values, ties, and ideals that come out in rough situations